Integration of Teaching and Research in Homoeopathy (Homoeopathy for All, 2022)
‘Teaching’ and ‘Research’ are two  important domains of academia  which need promotion and growth  independently for the benefit of  homoeopathic professionals of all  categories. Most of the academicians  believe in research- informed  teaching, since quality research  is essential for teaching of high  standard. The research activities  of the teaching faculty increase  knowledge currency, credibility,  competence in supervision and  motivation. It is an established fact  that research- informed teaching is  essential for high quality teaching.  Similarly, quality of research  methodology and outcomes depends  upon the educational background of  the researchers. The link between  teaching and research cannot be  established automatically. Rather,  an integrated teaching and research  environment has to be created in  the campuses of educational and  research institutions, with the efforts  of the policy makers, statutory and  regulatory bodies, universities and  support of the teaching faculty with  whole hearted cooperation of the  students – the ultimate beneficiaries
Keywords: Quality teaching; Quality research; Integrated teaching and research; Role of policy- makers and statutory/regulatory bodies